PENINGKATAN RELIGIUSITAS DAN PENDAPATAN KELUARGA MELALUI EKONOMI KREATIF PADA IBU RUMAH TANGGA DAN GENERASI MUDA DIKAWASAN BEKAS KERATON KARTASURA - Yulfan Arif Nurohman; Melia Kusuma; Fahri Ali Ahzar; Nur Wicaksono; Rina Sari Qurniawati (ABDI MAKARTI, 2022)
The area of the former Kartasura Palace has interesting tourism potential to be developed. One way to develop tourism potential is through the creative economy with the presence of special culinary delights that can increase interest in visiting the people of Solo and its surroundings. The potential of the community that can be developed in supporting a typical culinary business are housewives and the younger generation. The collaboration of housewives and the younger generation in developing a typical culinary business has the opportunity to be successful in the future. In order for the business to run smoothly, training is carried out for housewives and the younger generation in the area of the former Kartasura Palace.